The Success of Jewish Agricultural Colonies in Western Canada - Wilkinson, Eric (Hungarian Journal of English and American Studies, 2022)
This article assesses the history of Jewish agricultural settlements created in Western Canada in the late nineteenth and early twentieth centuries. The first settlements were founded following the 1881 Russian pogroms, at which time Canada’s Jewish community tried to resettle refugees in Western Canada. The result was the establishment of over a dozen farming colonies at the turn of the nineteenth and twentieth centuries. By examining the documentation produced by the colonists and the organizations that facilitated their settlement, it is possible to reconstruct the lives of the colonists in each community. This study investigates documents available for twelve different communities that span the Prairies. Settlers report several impediments to their success, including inexperience, poor soil, natural disaster, anti-Semitism, poor administration, and financial hardship. However, the decisive factor which brought an end to the colonies was upward social mobility. They were victims of their own success, unable to maintain their numbers as younger generations moved away, and parents joined them when they retired. The analysis of the farm colonies reveals the causes of their decline and provides grounds for re-evaluating their legacy. (EW)